2015
DOI: 10.1146/annurev-linguist-030514-125024
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and the Language Sciences

Abstract: Theories addressing the biological basis of language must be built on an appreciation of the ways that molecular and neurobiological substrates can contribute to aspects of human cognition. Here, we lay out the principles by which a genome could potentially encode the necessary information to produce a language-ready brain. We describe what genes are; how they are regulated; and how they affect the formation, function, and plasticity of neuronal circuits. At each step, we give examples of molecules implicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 128 publications
(164 reference statements)
0
30
0
1
Order By: Relevance
“…For understanding language evolution in particular, the genes involved in brain development and the vocal organs are of course especially interesting but, unfortunately, linking molecular genetics to language and speech is an extremely complex endeavor [18,19]. Thus, there has been only slow progress in understanding the functional implications of the non-coding differences between modern and archaic humans in the 'star' gene FOXP2 (such as the POU3F2 putative binding site in intron 8 [20]), but it seems likely that non-coding changes in this and other language-implicated genes such as ROBO1, ROBO2, and CNTNAP2 rose to high frequency after the separation of AMH from archaic hominins [21].…”
Section: The Human Treementioning
confidence: 99%
See 1 more Smart Citation
“…For understanding language evolution in particular, the genes involved in brain development and the vocal organs are of course especially interesting but, unfortunately, linking molecular genetics to language and speech is an extremely complex endeavor [18,19]. Thus, there has been only slow progress in understanding the functional implications of the non-coding differences between modern and archaic humans in the 'star' gene FOXP2 (such as the POU3F2 putative binding site in intron 8 [20]), but it seems likely that non-coding changes in this and other language-implicated genes such as ROBO1, ROBO2, and CNTNAP2 rose to high frequency after the separation of AMH from archaic hominins [21].…”
Section: The Human Treementioning
confidence: 99%
“…For example, some of these genes with fixed changes are expressed in the developing neocortex [16], other are involved in skin, hair and bone structure, while others affect the immune and reproductive systems [11,17 ]. Nevertheless, it is now possible to explore the function and evolutionary fate of archaic introgressions in a 'fossil-free' manner by examining the introgressions in modern populations [17].For understanding language evolution in particular, the genes involved in brain development and the vocal organs are of course especially interesting but, unfortunately, linking molecular genetics to language and speech is an extremely complex endeavor [18,19]. Thus, there has been only slow progress in understanding the functional implications of the non-coding differences between modern and archaic humans in the 'star' gene FOXP2 (such as the POU3F2 putative binding site in intron 8 [20]), but it seems likely that non-coding changes in this and other language-implicated genes such as ROBO1, ROBO2, and CNTNAP2 rose to high frequency after the separation of AMH from archaic hominins [21].…”
mentioning
confidence: 99%
“…I end with a brief discussion of the genetic basis for speech (for more detail, see Fisher 2017, Fisher & Vernes 2015, Pääbo 2014. Nothing is currently known about the physiological or genetic determinants of laryngeal descent or air sac loss, so I focus on the genetic determinants of neural mechanisms, where exciting progress has been made in the last two decades.…”
Section: Genetic Underpinnings Of Speechmentioning
confidence: 99%
“…The significance of inter-individual variation in linguistic abilities in the non-language-impaired population has only recently come to the fore in linguistics research, which has tended to focus on identifying those aspects of language acquisition and processing that are universal (Fisher and Vernes 2015). Some of this variation is due to environmental factors, and to stochastic effects in neurodevelopment, but multiple studies using twins and adoptees have shown that a large proportion of the variation is heritable (Stromswold 2001;Christopher et al 2013).…”
Section: Normal Variation and Exceptional Abilitiesmentioning
confidence: 99%